INNOVATIONS IN UI/UX DESIGN OF MOBILE APPLICATIONS: TRENDS, PRACTICES AND CHALLENGES - Afshan Jamal; Dr. Shazia Hashmat (Spectrum of Engineering Sciences, 2025)
As digital experiences rely more on mobile apps, the demand for interfaces and experiences that are both intuitive and focused on users has rapidly increased. Users now require more than conventional design approaches can provide in delivering responsive, accessible, and intelligent interactions. This study follows Review approach using PRISMA method, it covers 20 peer-reviewed publications issued from 2017 to 2024, which met our specific selection criteria. This review evaluates the latest advancements, important trends, leading practices, and ongoing problems in mobile UI/UX design, with a focus on themes including personalization, usability, accessibility, immersive technologies, and AI-driven approaches. The paper identifies ways in which AI is reshaping design, encompassing AI-powered personalization, adaptive interfaces, predictive analysis of user actions, and automated design generation as significant trends. Furthermore, AR, VR, and VUIs are found to boost user interest and accessibility by providing richly engaging and non-intrusive interactions. The results point to UCD, iterative testing, performance optimization, and a commitment to inclusive accessibility standards as major principles. Frameworks that support multiple platforms, for example Flutter and React Native, are becoming the preferred choice for delivering both consistency and scalability. Despite the important enhancements noted, challenges persist mainly in the form of restricted screen sizes, increased mental demands, keeping designs consistent across platforms, and incorporating advanced technologies. This review summarizes a comprehensive framework aimed at various players in the mobile UI/UX field, illustrating the value of interdisciplinary efforts, responsible design, and flexible approaches for advancing mobile UI/UX development.